Validasi Metode Penetapan Kadar Dekstrometorfan Hidrobromida, Gliseril Guaiakolat dan Klorfeniramin Maleat secara Kromatografi Cair Kinerja Tinggi serta Aplikasinya dalam Sediaan Tablet Obat Batuk - Khoirul Anwar; Khamdan Muhaimin Zuhdi; Sugito Candra (LPPM Universitas Abdurrab, 2026)
Cough is a natural defense mechanism that functions to clear secretions and foreign particles from the respiratory tract. Allergic cough is commonly treated with a combination of dextromethorphan hydrobromide, glyceryl guaiacolate, and chlorpheniramine maleate. This study aimed to develop and validate a High-Performance Liquid Chromatography (HPLC) method for the simultaneous determination of these compounds in tablet dosage forms. The HPLC method employed a reversed-phase system using a C18 column with a mobile phase consisting of methanol : acetonitrile : distilled water (20:5:75, v/v), a flow rate of 1.0 mL/min, and UV detection at 270 nm. Method validation was performed in accordance with analytical guidelines, including linearity, sensitivity (LOD and LOQ), selectivity, precision, and accuracy. The results demonstrated good linearity for all analytes with correlation coefficients (r) greater than 0.998. The LOD and LOQ values met the required criteria. Precision studies showed %RSD values ≤ 2%, while accuracy ranged from 99% to 101%. Assay results of two commercial tablet samples complied with pharmacopeial requirements. The validated HPLC method proved to be accurate, precise, selective, and suitable for routine analysis of dextromethorphan hydrobromide, glyceryl guaiacolate, and chlorpheniramine maleate in tablet formulations.